The increase of radiation doses due to exploration activities in Yen Phu rare earth deposit, Yen Bai province, Northern Vietnam - Le Khanh Phon, Le Khanh; Huong, Phan Thien; Pieczonka, Jadwiga; piestrzynski, Adam; Chau, Nguyen Dinh; Bich, Vu Van; Nhien, Tran Thien; Son, Nguyen Thai; Duyen, Nguyen Thi Thu (Vietnam Journal of Marine Science and Technology, 2017)
Yen Phu rare earth deposit covering over 0.7 km2 in Yen Bai province, Northern Vietnam contains heavy elements bearing radioactive materials. The area has been studied based on data of several thousand meters of boreholes, 2000 m3 of trenches, shallow shafts, and thousands of rock samples. This article shows the results of radioactive measurements and analysis by regular grids before and after exploration activities. The investigated area has been divided into two different subunits characterized by different levels of the radiation dose. It can be observed that after the exploration process, equivalent dose increases by 1.2 mSv/y and reaches recent value of 9.9 mSv/y. This value is still below the acceptable value according to the ICRP regulations, however, it should be noted that the increase can exceed the critical value during industrial production and processing. Therefore it will be necessary to undertake investigation and implementation of radioactive monitoring system to maintain the safety for people.